An iron(ii) spin-crossover metallacycle from a back-to-back bis-[dipyrazolylpyridine]1. Issue 20 (28th May 2015) - Kershaw Cook, Laurence J.; Fisher, Julie; Harding, Lindsay P.; Halcrow, Malcolm A.
<x xml:space="preserve">Abstract</x> Iron(ii) and zinc(ii) complexes of bis[2, 6-di(pyrazol-1-yl)pyrid-4-yl]disulfide assemble into tetranuclear metallacycles according to ES-MS, DOSY NMR and conductivity data. The iron complex exhibits a thermal spin-state equilibrium in solution, which the iron centres appear to undergo independently of each other.